ENETWILD training: "First online course on the use of camera trapping for monitoring wildlife and density estimation in the framework of the European Observatory of Wildlife (5th May 2022). Issue 6 (20th June 2022) - ,; Casaer, J; Palencia, P; Vicente, J; Acevedo, P; Jansen, P; Rowcliffe, M; Guerrasio, T; Scandura, M; Apollonio, M; Blanco, JA
Abstract: One of the main objectives of ENETWILD consortium is to collect data on density, hunting statistics and wildlife occurrence in order to model the geographical distribution and abundance of wildlife species across Europe as a tool to support the assessment of risks associated, for example, with disease transmission. Created in the framework of the ENETwild project, the European Wildlife Observatory (EOW 2 ) provides the backbone for an integrated, interdisciplinary, multi‐sectoral and multi‐institutional approach to wildlife monitoring, initially focusing on terrestrial mammals in Europe. The EOW applies similar camera‐trapping‐based protocols for population estimation and data collection standards to facilitate harmonization and interoperability. For this purpose, continuous training of the network of wildlife professionals in Europe is a key activity of the EOW. In this context, during the last few years the ENETWILD consortium has organized different online training courses and workshops on the use of camera traps, addressing different approaches from the design and handling of camera traps to the processing of the collected data. Many of the participants in our previous courses are now part of the EOW and require updated information on methodology to process with next steps in the field. The course here reported presented improvements and refinements in the sampling protocols, aimed specially at new collaborators to be incorporated in the network. Therefore, the objectives of this introductory online course held on 5 th May 2022 were: (i) to present milestones and achievements of the ENETWILD project and the EOW, and (ii) to review scientific methods for determining wildlife abundance and density, providing specific training on camera trapping methods and protocols, specifically the random encounter method (REM) and other methods which do not require identification of individuals. This course was attended by 46 wildlife biologists, animal health professionals and wildlife experts from national hunting and forestry authorities. Detailed explanations, protocols, and examples for applying such protocols were provided.